2020
DOI: 10.1029/2019wr026724
|View full text |Cite
|
Sign up to set email alerts
|

Calibrated Simulation of the Long‐Term Average Surficial Groundwater System and Derived Spatial Distributions of its Characteristics for the Contiguous United States

Abstract: While the physical processes governing groundwater flow are well understood, and the computational resources now exist for solving the governing equations in three dimensions over continental‐scale domains, there remains substantial uncertainty about the subsurface distribution of the properties that control groundwater flow and transport for much of the contiguous United States (CONUS). The transmissivity of the shallow subsurface is a key parameter for the simulation of water table position, shallow groundwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 35 publications
1
30
0
1
Order By: Relevance
“…However, the relative contributions of vertical and lateral flows to net inflow are poorly understood (Butler et al, 2016(Butler et al, , 2020b.While recent work has found that reductions in aquifer net inflow can decrease the effectiveness of groundwater conservation programs over time (Butler et al, 2020b), it is highly uncertain how the mechanisms, timescales, and magnitudes of lagged responses from different water balance components vary. For example, estimates of the magnitude and transit time for groundwater recharge vary dramatically over the HPA due to thick unsaturated zones (Gurdak et al, 2008;Katz et al, 2016;McMahon et al, 2006;Zell & Sanford, 2020). As a result, we do not know which lagged responses may impact overall groundwater sustainability, nor the timescales and controlling processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relative contributions of vertical and lateral flows to net inflow are poorly understood (Butler et al, 2016(Butler et al, , 2020b.While recent work has found that reductions in aquifer net inflow can decrease the effectiveness of groundwater conservation programs over time (Butler et al, 2020b), it is highly uncertain how the mechanisms, timescales, and magnitudes of lagged responses from different water balance components vary. For example, estimates of the magnitude and transit time for groundwater recharge vary dramatically over the HPA due to thick unsaturated zones (Gurdak et al, 2008;Katz et al, 2016;McMahon et al, 2006;Zell & Sanford, 2020). As a result, we do not know which lagged responses may impact overall groundwater sustainability, nor the timescales and controlling processes.…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater/surface-water modeling: The Center will use a cutout of the National Groundwater Model (NGWM; Zell and Sanford, 2020) to simulate transient groundwater flow, groundwater/surface-water interactions, and nitrogen loading from groundwater discharge to streams. The NGWM is an innovative, MODFLOW 6 based model of the shallow groundwater system for the contiguous United States.…”
Section: Science Capabilities and Advancement Opportunitiesmentioning
confidence: 99%
“…Given the strengths of regional models, a potential alternative to development of large-scale groundwater models would be combining or aggregating multiple regional models in a patchwork approach (as in Zell and Sanford, 2020) to provide global coverage. This would have the advantage of better respecting regional differences but potentially create additional challenges because the regional https://doi.org/10.5194/gmd-2021-97 Preprint.…”
Section: Synergies Between Regional-scale and Large-scalesmentioning
confidence: 99%